Articulating food security and sustainable agriculture - International Food Policy Research Institute (International Food Policy Research Institute, 2018)
The environmental and food security-related challenges faced by the world today urgently require collective action. Global food production will have to increase by 60 percent by 2050 in order to feed the growing global population and ensure food security for all. In addition, this increased production must happen in a sustainable manner to protect the world’s already scarce natural resources—soil, land, water, and ecosystems—from further depletion and degradation. Increasing sustainable agricultural production will require continuous research and development (R&D) for new technologies and innovations in climate-smart agriculture (CSA). Developing these technologies and bringing them to scale, however, will require significant financial investment from both the public and the private sectors, as well as an open and efficient agricultural trade system.